2017
DOI: 10.1109/joe.2016.2565018
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-Based Offshore Wind Resource Assessment in the Mediterranean Sea

Abstract: Identification of prominent sea areas for the efficient exploitation of offshore wind energy potential requires primarily the assessment and modeling of several aspects of the long-term wind climate. In this work, the offshore wind speed and wind direction climate of the Mediterranean Sea is analytically described, the corresponding offshore wind energy potential is estimated on an annual and seasonal basis, and candidate areas for potential offshore wind farm development are identified. The analysis is based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…However, the approach has not accounted for bottom depth that is a major technical restriction; see Figure 12, where the mean annual offshore wind power density at 80 m height above sea level (asl) according to the results obtained from an atmospheric ETA-based model is presented, and Figure 13 below, where the locations satisfying the depth restrictions are depicted. An offshore wind potential assessment in the MS, taking into account bottom depth restrictions, has been also recently performed in [148] using the Blended Sea Winds (BSW) satellite dataset from the US National Oceanic and Atmospheric Administration (NOAA). The data cover the period from 1995 to 2011.…”
Section: Offshore Wind Resource Availabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, the approach has not accounted for bottom depth that is a major technical restriction; see Figure 12, where the mean annual offshore wind power density at 80 m height above sea level (asl) according to the results obtained from an atmospheric ETA-based model is presented, and Figure 13 below, where the locations satisfying the depth restrictions are depicted. An offshore wind potential assessment in the MS, taking into account bottom depth restrictions, has been also recently performed in [148] using the Blended Sea Winds (BSW) satellite dataset from the US National Oceanic and Atmospheric Administration (NOAA). The data cover the period from 1995 to 2011.…”
Section: Offshore Wind Resource Availabilitymentioning
confidence: 99%
“…An offshore wind potential assessment in the MS, taking into account bottom depth restrictions, has been also recently performed in [148] using the Blended Sea Winds (BSW) satellite dataset from the US National Oceanic and Atmospheric Administration (NOAA). The data cover the period from 1995 to 2011.…”
Section: Offshore Wind Resource Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…in the Mediterranean Sea. 87 The authors found that the offshore wind power potential in the Mediterranean Sea is the highest in the Gulf of Lyon (mean annual wind power density up to ß1600 Wm -2 ) and the Aegean Sea (with mean annual wind power density up to ß1150 Wm -2 ).…”
Section: Studies Of Offshore Wind and Power In Europe Under Present Cmentioning
confidence: 99%
“…Twenty years of offshore wind data from the Blended Sea Winds product, provided by the U.S. National Oceanic and Atmospheric Administration, were used to estimate offshore wind resources at 10 m a.s.l. in the Mediterranean Sea . The authors found that the offshore wind power potential in the Mediterranean Sea is the highest in the Gulf of Lyon (mean annual wind power density up to ∼1600 Wm –2 ) and the Aegean Sea (with mean annual wind power density up to ∼1150 Wm –2 ).…”
Section: Determination Of the Best Locations From A Physical Point Ofmentioning
confidence: 99%